2017
DOI: 10.1109/tbcas.2017.2749304
|View full text |Cite
|
Sign up to set email alerts
|

Blood Quality Diagnostic Device Detects Storage Differences Between Donors

Abstract: In 2013, nearly 15 million units of banked blood were transfused in the United States alone. Blood shortages are expected to increase globally. Donated blood is not equal due to differences in quality and deterioration rate. There are no methods to detect time-dependent biochemical and biophysical changes of RBCs or the deterioration rate of donated RBCs. Nine randomly selected RBC units collected by the San Diego Blood Bank were examined for inter-donor variability over six weeks of storage. In vitro RBC qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…RBC deformability measured using the microfluidic ratchet revealed significant inter-donor variability of freshly collected RBCs as well as inter-donor variability in RBC rigidification during storage. Interestingly, while previous efforts have reported storage-mediated mechanical deterioration of RBCs, deformability of fresh RBCs has largely been reported to be invariant 56,57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RBC deformability measured using the microfluidic ratchet revealed significant inter-donor variability of freshly collected RBCs as well as inter-donor variability in RBC rigidification during storage. Interestingly, while previous efforts have reported storage-mediated mechanical deterioration of RBCs, deformability of fresh RBCs has largely been reported to be invariant 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…RBC deformability is a key part of the mechanism for splenic clearance of RBCs 50,51 , and has therefore been frequently proposed as a potential biomarker for estimating the clearance time of transfused RBCs 52,53 . Traditional methods, such as ektacytometry 28,29,54,55 , test the rheological properties of RBC derived from bulk flow, which does not correlate well with circulatory clearance time 56,57 . Microfluidic technologies present the potential to improve upon this measurement process by using microfabricated structures to approximate the deformation mechanics of the splenic microvasculature [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that RBCs undergo time dependent changes that impair deformability and various biochemical properties, namely pH, ATP, and 2,3 DPG concentration, known as storage lesion. While decay in biochemical properties is uniform across multiple populations of RBCs, our group has recently demonstrated that changes in deformability are variable and donor dependent (Jani et al, 2017a). As lipids are the most compliant of biomolecules, an increase of lipid oxidation injury and subsequent increase in membrane cell density during storage result in decreased compliance.…”
Section: Discussionmentioning
confidence: 99%
“…RBC deformability is a key part of the mechanism for splenic clearance of RBCs 50,51 , and has therefore been frequently proposed as a potential biomarker for estimating the clearance time of transfused RBCs 52,53 . Traditional methods, such as ektacytometry 28,29,54,55 , test the rheological properties of RBC derived from bulk flow, which does not correlate well with circulatory clearance time 56,57 . Microfluidic technologies present the potential to improve upon this measurement process by using microfabricated structures to approximate the deformation mechanics of the splenic microvasculature [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%